Reformasi Pendidikan Islam oleh Mahmud Yunus: Integrasi Ilmu Agama dan Umum dalam Kurikulum Modern - Wardhana, Muhammad Galih Kusuma; Baidi, Baidi (TSAQOFAH, 2025)
This study aims to examine the contributions of Mahmud Yunus to the modernization of Islamic education in Indonesia through a library research approach. Mahmud Yunus was a reformist figure who played a significant role in integrating Islamic values with modern scientific knowledge within the national education system. The study reveals that his educational thought encompassed the renewal of an integrated curriculum, the development of teaching methods that emphasize rational, spiritual, and practical dimensions, and the establishment of modern Islamic educational institutions. He also highlighted the crucial role of teachers in shaping students’ character and fostering a learning environment grounded in noble morals. The findings indicate that Mahmud Yunus’s ideas remain relevant as a foundation for developing Islamic education that is responsive to the challenges of modern times while upholding ilahiyah values as its core. This conclusion contributes theoretically to the discourse on Islamic education reform and offers practical implications for curriculum development and instructional strategies in contemporary Islamic educational institutions.